Administrative protection of young people in Iraq Comparative study with the United Arab Emirates - المخزومي, وليد مرزة; مجيد, ايلاف سعيد (Journal of Legal Sciences, 2021)
Because of what Iraq faced in the last quarter of the last century of wars and military conflicts and the aftermath of the economic blockade, as well as the recent occupation suffered by Iraq in the contemporary century, which culminated in lawlessness and the spread of terrorism and the most prominent on the Iraqi street manifestations not prepared before paved to the aggravation and collapse in the community system As a result of the political and social changes, all this highlighted the need for public facilities specialized in social protection for young people to provide all the new requirements, and the find a legal system commensurate with the circumstances and circumstances.In light of the current challenges, the State has a duty to provide all the necessary requirements for the young population by all possible means in fulfillment of the national duty of care and protection for all citizens, and in fulfillment of its international obligations as an integral part of the international community, During the research, through the statement of the most important activities performed by social protection facilities for young people and review the competent administrative authorities to undertake this activity, and try to review the most important legislation that is the basis for administrative protection provided to this category and what may march Defects or deficiencies, in comparison with the United Arab Emirates.